1991
DOI: 10.1093/nar/19.13.3533
|View full text |Cite
|
Sign up to set email alerts
|

Viral RNA annealing activities of the nucleocapsid protein of Moloney murine leukemia virus are zinc independent

Abstract: The zinc fingers of retroviral gag nucleocapsid proteins (NC) are required for the specific packaging of the dimeric RNA genome into virions. In vitro, NC proteins activate both dimerization of viral RNA and annealing of the replication primer tRNA onto viral RNA, two reactions necessary for the production of infectious virions. In this study the role of the zinc finger of Moloney murine leukemia virus (MoMuLV) NCp10 in RNA binding and annealing activities was investigated through modification or replacement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 46 publications
4
71
0
Order By: Relevance
“…Experiments have shown that the binding of tRNA 3 Lys to the primer-binding site and the dimerization of sequences containing the ⌿ site require only peptides outside of the zinc fingers, including the basic backbone residues (55,59). It is known that the basic residues of NC are vital for RNA binding in vitro (73).…”
Section: Mutant Nc Proteins Display Differing Effects On Annealing Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments have shown that the binding of tRNA 3 Lys to the primer-binding site and the dimerization of sequences containing the ⌿ site require only peptides outside of the zinc fingers, including the basic backbone residues (55,59). It is known that the basic residues of NC are vital for RNA binding in vitro (73).…”
Section: Mutant Nc Proteins Display Differing Effects On Annealing Dmentioning
confidence: 99%
“…A number of investigators have completed annealing assays with mutant NC proteins to determine what residues are necessary for NC chaperone capability. Studies examining the effect of Moloney murine leukemia virus (MMLV) NC mutants on the annealing of tRNA Pro to MMLV RNA, as well as the dimerization of the genomic RNA segments, showed that the basic regions of NC are necessary for enhancement (55,56). These studies indicated that the single zinc finger of MMLV NC could be removed and that chaperone activity was retained.…”
mentioning
confidence: 99%
“…NC is a nucleic acid chaperone and catalyzes conformational rearrangements that lead to the most thermodynamically stable structures (19 -30). The NC domain in Gag promotes tRNA primer placement on the RNA genome (31,32), although the NC protein itself also has this activity in vitro (32)(33)(34)(35)(36)(37). The zinc fingers are not required for the tRNA annealing reaction, either in vitro (34 -37) or in vivo (31).…”
mentioning
confidence: 99%
“…These effects were first reported by Prats et al (1991), who found that the zinc finger motif in the nucleocapsid protein of Moloney murine leukaemia virus (MoMLV) was dispensable for RNA binding in vitro despite modifications that destroy the affinity of the motif for Zn 2+. Instead, a pair oflysines adjacent to the zinc finger motif, in positions analogous to those of the lysine and arginine residues substituted in 7b mutant BM26 (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Another similarity to the BSMV 7b results was that mutations in the MoMLV nucleocapsid zinc finger motif, like those in the C1 and C2 clusters, had no obvious effects on RNA associations in vitro. From these results, Prats et al (1991) postulated that interactions of the finger motif with zinc influence the conformation requirements of the nucleocapsid protein for specific packaging of the retroviral RNA genome. Additional studies that are relevant to our findings with BSMV suggest that the human immunodeficiency virus (HIV) nucleocapsid protein, which contains two zinc finger-like motifs flanked by basic amino acid residues, has RNA annealing activities that are independent of the activity of the two zinc fingers (Berkowicz et al, 1993;Berkowicz & Goff, 1994;De Rocquigny et al, 1992;Summers et al, 1992).…”
Section: Discussionmentioning
confidence: 99%